Scoring system for the diagnosis of bilateral primary aldosteronism in the outpatient setting before adrenal venous sampling. (19th December 2016) - Kobayashi, Hiroki; Haketa, Akira; Ueno, Takahiro; Ikeda, Yukihiro; Hatanaka, Yoshinari; Tanaka, Sho; Otsuka, Hiromasa; Abe, Masanori; Fukuda, Noboru; Soma, Masayoshi
Summary: Objective: The only reliable method for subtyping primary aldosteronism (PA) is adrenal venous sampling (AVS), which is costly and time‐consuming. Considering the limited availability of AVS, it would be helpful to obtain information on the diagnosis of bilateral hyperaldosteronism (BHA) from routine tests. We aimed to establish new, simple criteria for outpatients to diagnose BHA from PA before AVS. Design: We retrospectively analysed 82 patients who were diagnosed with PA and underwent AVS. Thirty‐seven patients were diagnosed with unilateral hyperaldosteronism (UHA), and 36 with BHA and nine were undetermined. Among the variables that were significantly different between UHA and BHA in the univariate analysis, we chose three variables to be included in multivariate logistic regression models and constructed a subtype prediction score. Results: The subtype prediction score was calculated as follows: 3 points for no adrenal nodules on computed tomography imaging, 2 for serum potassium of ≥3·5 mmol/l and 2 for aldosterone‐to‐renin ratio of <490 after a captopril challenge test. Receiver operating characteristic curve analysis for the ability to discriminate BHA from UHA showed that a score of 7 points had 50% sensitivity and 100% specificity and a score of 5 points had 67% sensitivity and 94% specificity (area under the curve: 0·922; 95% CI: 0·863–0·980). Conclusions: Our new, simple criteria specifically distinguished BHA from UHA in the outpatient setting before AVS. Furthermore, not only endocrinologists but also general internists can use this convenient, safe scoring system.